The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.tmaid.2019.04.010
|View full text |Cite|
|
Sign up to set email alerts
|

Respiratory and gastrointestinal infections at the 2017 Grand Magal de Touba, Senegal: A prospective cohort survey

Abstract: Background: The Grand Magal of Touba is the largest Muslim pilgrimage in Senegal with a potential for infectious disease transmission. Methods: Clinical follow-up, adherence to preventive measures and qPCR-based respiratory and gastrointestinal pathogens carriage pre-and post-Magal, were assessed. Results: 110 pilgrims from South Senegal were included. The duration of stay in Touba was 3 days. 41.8% and 14.5% pilgrims reported respiratory and gastrointestinal symptoms. Most individuals having the onset of symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 22 publications
(33 reference statements)
2
16
0
Order By: Relevance
“…It is well-known that mass gatherings are seeding events to spread outbreaks of communicable diseases (Hoang et al, 2019;Sokhna et al, 2017;Sow et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that mass gatherings are seeding events to spread outbreaks of communicable diseases (Hoang et al, 2019;Sokhna et al, 2017;Sow et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed all available diagnoses of respiratory viruses including SARS-CoV-2 performed between September 2013 and May 2020 at the clinical microbiology and virology laboratory of University Hospital Institute Méditerranée Infection ( https://www.mediterranee-infection.com/ ) and University hospitals of Marseille, the second largest French city, Southeastern France. Testing of respiratory samples were performed using the FTD Respiratory pathogens 21 (Fast Track Diagnosis, Luxembourg), the Biofire FilmArray Respiratory panel 2 plus (Biomérieux, Marcy-l'Etoile, France), the Respiratory Multi Well System r-gene (Argene, BioMérieux), or the GeneXpert Xpert Flu/RSV (Cepheid, Sunnyvale, CA) assays, or by one-step simplex real-time quantitative RT-PCR amplifications as previously reported ( Hoang et al, 2019 ). Diagnosis by reverse transcription-PCR of SARS-CoV-2 infection was performed as previously described ( Amrane et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Syndromic surveillance studies conducted on Grand Magal pilgrims over recent years have demonstrated that respiratory tract infections are among the most frequent causes of consultations at health care structures during the event [ 1 ]. A prospective cohort study showed that the prevalence of respiratory tract infection symptoms was 42% among pilgrims with a 5-fold increase following the participation to the Grand Magal [ 2 ]. Common coronaviruses were the most frequently acquired respiratory viruses [ 2 ].…”
mentioning
confidence: 99%
“…A prospective cohort study showed that the prevalence of respiratory tract infection symptoms was 42% among pilgrims with a 5-fold increase following the participation to the Grand Magal [ 2 ]. Common coronaviruses were the most frequently acquired respiratory viruses [ 2 ]. The occurrence of a dengue outbreak in Touba during the 2018 Grand Magal raised the risk for further spread to other regions in Senegal through viremic Mourid pilgrims returning to their place of residence where Aedes mosquitoes are present [3] .…”
mentioning
confidence: 99%